A Taxonomy of Software Delivery Performance Profiles: Investigating the Effects of DevOps Practices - Rothenberger, Marcus A.; Humble, Jez; Thatcher, Jason Bennett; Smith, Dustin; Forsgren, Nicole (2020 (AMCIS) Americas Conference on Information Systems, 2020)
This research develops a taxonomy of Software Delivery Performance Profiles for DevOps development settings. We base the underlying Software Delivery Performance measure on the application of the Economic Order Quantity (EOQ) model to software development. Consistent with the objectives of both, development and operations departments, the measure includes attributes for throughput (release frequency and lead-time to delivery) and for stability (mean time to restore). Hierarchical cluster analysis on a global sample of 7,522 DevOps professionals results in three distinct Software Delivery Performance Profiles; in addition, the results indicate that the measures for throughput and stability move in tandem. Further analysis will show how the use of individual DevOps practices impacts Performance Profiles of development settings. When completed, the study will support the utility of DevOps and the effectiveness of individual DevOps practices.